À contre-courant : les mobilités caribéennes vers l’Éthiopie - Giulia Bonacci (Études Caribéennes)
The article deals with Caribbean migration towards Ethiopia, and especially the one of Rastafarians who define themselves as ‘true Ethiopians’ and ‘repatriates’ in Ethiopia. Despite their limited number, their experience is nonetheless important as it reveals the persistence and change in imaginaries and ideologies linking black all over the world to Ethiopia as well as unknown Caribbean mobility towards Africa, a mobility which is driven against the current.